Theme Realization in Everything, Everything Movie Script - Tarigan, Nurhayati; Sinar, T. Silvana; Harefa, Yulianus; Yusuf, Muhammad (LPPM Universitas Mercu Buana Yogyakarta, 2019)
There are two kinds of Theme: Unmarked Theme and Marked Theme. It is divided into two subtypes: simple Theme and multiple Theme. The theory of Systemic Functional Linguistics (SFL) is used, regarded with textual function that observes clause as a message and analyzes it from the thematic structure in the term of Theme-Rheme. The method of descriptive qualitative is applied. The source of data were Everything, Everything movie script, taken from Springfield Springfield site. Data of the research were selected, based on the second character dialog. The purpose of this research is to indicate the types and to describe the realization of the Theme markedness. The research findings showed, the dominant type of markedness realization is simple unmarked Theme with 69.4% percentage. It dominates the other markedness realization, that is simple marked Theme with 2.4% percentage, multiple unmarked Theme with 27.1% percentage, and multiple marked Theme with 0.9% percentage.